Antitumor activities of carboplatin–doxorubicin–ZnO complexes in different human cancer cell lines (breast, cervix uteri, colon, liver and oral) under UV exposition - Suttirak Pairoj; Pattareeya Damrongsak; Badin Damrongsak; Natini Jinawath; Rossukon Kaewkhaw; Chinnapat Ruttanasirawit; Tanaporn Leelawattananon; Kitsakorn Locharoenrat (Artificial Cells Nanomedicine and Biotechnology, 2021)
of 0.137 µg/mL, whereas the loading capacity and efficiency of CP-DOX-ZnO were 77.81% and 99.05%, respectively. Fluorescence images confirmed that CP-DOX-ZnO using DOX served as a fluorescence enhancer specifically bound onto the cell membranes, which became almost saturated after 24 h incubation. Carboplatin-DOX-ZnO was possibly endocytosed by cancer cells and was selectively internalized into the target cells; thus, free chemo drug was released in the cytoplasm, which induced acute apoptosis. This resulted in complete inhabitation of growth signal of target cancer cells.
Keywords: Nanoplatforms for cancer theranostics; Metal complexes synthesis and properties; Synthesis and Characterization of Heterocyclic Compounds